2000
DOI: 10.1159/000055910
|View full text |Cite
|
Sign up to set email alerts
|

Increased Cell Surface Expression of Receptors for Transforming Growth Factor-β on Osteoblasts from Patients with Osteogenesis imperfecta

Abstract: Osteogenesis imperfecta (OI) is a heritable connective tissue disorder usually characterized by either a reduction in the production of normal collagen I or the synthesis of abnormal collagen. The variability in the clinical phenotype is not in each case sufficiently explained by the underlying mutation in the collagen I genes. Also, biochemical differences between mutant collagen from different tissues suggest additional regulatory mechanisms possibly involved in matrix deposition and maturation, two processe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
12
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 28 publications
5
12
0
Order By: Relevance
“…In the present study, we found higher gene expression levels of TGF‐β receptor I and II, suggesting elevated TGF‐β signaling due to a higher amount of TGF‐β receptors. This is in line with in vitro TGF‐β binding studies showing that osteoblasts from individuals with OI type I and IV have a higher number of TGF‐β receptors on the cell surface than age‐matched controls . It is, therefore, possible that in OI increased TGF‐β signaling is not only due to disturbed bone matrix but also due to increased TGF‐β receptor levels in osteoblasts.…”
Section: Discussionsupporting
confidence: 82%
“…In the present study, we found higher gene expression levels of TGF‐β receptor I and II, suggesting elevated TGF‐β signaling due to a higher amount of TGF‐β receptors. This is in line with in vitro TGF‐β binding studies showing that osteoblasts from individuals with OI type I and IV have a higher number of TGF‐β receptors on the cell surface than age‐matched controls . It is, therefore, possible that in OI increased TGF‐β signaling is not only due to disturbed bone matrix but also due to increased TGF‐β receptor levels in osteoblasts.…”
Section: Discussionsupporting
confidence: 82%
“…OI bone cells do not exhibit a TGF-␤-dependent increase in collagen synthesis and alkaline phosphatase activity seen with normal bone cells (48). OI osteoblasts had a greater reduction in TGF-␤ receptor I-III number than agematched controls, and receptor affinity was unchanged, whereas ligand-induced modulation of receptor number was found to be impaired in the OI cells (49). Thus, the association of elevated thrombospondin levels with altered post-translational modifications in OI osteoblasts is unlikely to involve TGF-␤.…”
Section: Resultsmentioning
confidence: 83%
“…Additionally, TGF‐β1 circulating levels and bone expression are upregulated during CKD progression along with increased sclerostin and FGF23 . Elevated TGF‐β activity is also associated with enhanced osteoblast and/or osteoclast activity in genetic bone diseases such as Camurati‐Engelmann disease (CED) and osteogenesis imperfecta (OI) . Finally, TGF‐β and Wnt/β‐catenin cross‐talk has been well described …”
Section: Discussionmentioning
confidence: 99%